Colombia : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Colombia's Arrangement Under the Flexible Credit Line (FCL) and Cancellation of the Current Arrangement. In the baseline scenario, growth in Colombia is expected to decelerate to 3.4 percent in 2015 but gradually return toward potential over the medium term and inflation to remain at the midpoint of the central bank's 2-4 percent target range. The authorities are requesting a successor two-year FCL arrangement for 500 percent of quota, and cancellation of the current arrangement which expires on June 23, 2015. The IMF staff assesses that Colombia meets the qualification criteria for access to IMF resources under the FCL arrangement, and recommends its approval by the Executive Board.